(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article analyzes the personal concept of Professor, Doctor of Philological Sciences Begali Kasimov, as well as the scientist’s articles, such as fidelity to the truth, impartial analysis of the problems of Uzbek literature during the period of national Renaissance, preparation of high-quality textbooks, expressed higher and comprehensive schools, presentation of Uzbek science to the world.